Modern estimation of oil and gas potential prospects and priority directions for the search for new hydrocarbon deposits on the Black Sea shelf of the Prykerchensky shelf - B. M. Polukhtovich; V. V. Gladun; T. E. Dovzhok; P. Ya. Maksymchuk; S. M. Zakharchuk; P. M. Melnichuk; T. M. Galko; O. V. Volkova; V. P. Klochko (Геофизический журнал, 2012)
Drilling of parametric Subbotina-403 well in the Ukrainian sector of Kerch shelf of the Black Sea conducted in 2004-2006 was marked by the first oil gusher within water areas of Ukraine. Kerch-Taman (Pivdennokerchenskyy) flexure with zones of anticline folds of northeast strike after preliminary assessment of resources in 2004 was enriched with a new oil field Subbotina and deserves a modern assessment of the prospects of oil and gas. On this basis reasonable priorities of geological and geophysical exploration are substantiated.